Progress in exercise interventions for autism spectrum disorder: exploring underlying mechanisms - Wang, Chaofan; Zhang, Yuanxiang; Zhu, Jimiao; Lin, Zhiyi (Frontiers in Psychiatry, 2026)
ASD is a neurodevelopmental disorder with specific core symptoms. Physical activity has been demonstrated to positively influence the pathological mechanisms underlying autism and to alleviate associated symptoms. A comprehensive synthesis was conducted by reviewing and integrating relevant literature. Literature review revealed that the mechanism of physical activity intervention in autism primarily involves modulation through neuronal factors, glial cells, and gut microbiota. Neuronal factors include brain-derived neurotrophic factor, axonal protein families, and neurotransmitters. Additionally, physical activity helps alleviate stereotypical behaviors and internal anxiety in individuals with ASD, reduce obesity and cardiovascular diseases in some patients, and enhance social communication skills.